2017
DOI: 10.33546/bnj.75
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Moringa Oleifera on Level of Prolactin and Breast Milk Production in Postpartum Mothers

Abstract: Background: Breastfeeding among postpartum mothers has been a problem due to low milk supply. As a result, mothers often decide to give formula milk or other additional foods, which might affect to the infant’s growth and development.Objective: This study aims to investigate the effect of Moringa Oliefera on the levels of prolactin and breast milk production (baby’s weight and sleep duration) in postpartum mothers. Methods: Quasi-Experimental study with Non Equivalent control group design. There were 30 respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 8 publications
0
9
0
7
Order By: Relevance
“…Moreover, prolactin and estrogen have been recognized to result in upregulation of AQP1, AQP3, and AQP5 expression [24][25][26]. The individual plants in PHF are known for their ability to increase milk production in animal models and in humans by stimulating lactating hormones [27][28][29][30]. A previous study suggested that levels of prolactin and oxytocin were higher in lactating BALB/C mice supplemented with S. androgynus leaf extract [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, prolactin and estrogen have been recognized to result in upregulation of AQP1, AQP3, and AQP5 expression [24][25][26]. The individual plants in PHF are known for their ability to increase milk production in animal models and in humans by stimulating lactating hormones [27][28][29][30]. A previous study suggested that levels of prolactin and oxytocin were higher in lactating BALB/C mice supplemented with S. androgynus leaf extract [28].…”
Section: Discussionmentioning
confidence: 99%
“…An estrogen-like effect or phytoestrogen and diosgenin (a type of steroidal sapogenin) in fenugreek or T. foenum-graceum have been considered as responsible compounds for the galactagogue effect in this herb [4]. Moringa oleifera also possesses the ability to increase prolactin levels and milk production in mothers supplemented with M. oleifera compared with the control group [27,29].…”
Section: Discussionmentioning
confidence: 99%
“…For example, chaya (which originated in Mexico and Mesoamerica) protects the heart, liver, and kidneys from toxin damage [47,48]; drumstick (India and Pakistan) has anti-bacterial effects [49,50]; and bele (Papua New Guinea and Solomon Islands) is used for bone repair and treating osteoporosis [51]. Hedge panax, drumstick, chaya, bele, and purslane are galactogogues that can stimulate lactation [10,[52][53][54]. Indeed, purslane's generic name Portulaca means "to carry milk".…”
Section: Medicinal Effectsmentioning
confidence: 99%
“…Berdasarkan penelitian Zakaria dkk (2015) pemberian ekstrak daun kelor berpotensi meningkatkan kadar Hb sehingga menurunkan anemia ibu, walaupun kadar besi susu tidak meningkat secara signifikan. Sedangkan penelitian Sulistyawati (2017) (Fikawati, 2010). Agar bayi optimal mendapatkan ASI ma diperlukan beberapa kiat menuju keberhasilan antara lain usahakan memberi minum dalam suasana yang santai bagi ibu dan bayi.…”
Section: Pendahuluanunclassified